Is There a Programmatic Vote in Elections in Weak Political Party Systems? An Analysis of the 2016 Peruvian Presidential Election - Sulmont, David (Revista de Ciencia Política, 2018)
This paper analyzes the importance of programmatic differences between political parties in guiding electoral choices among voters. Even in circumstances of low party system institutionalization and high electoral volatility, citizens can differentiate politicians’ different programmatic stances on controversial issues and decide their vote according to their own preferences. Using the Peruvian presidential elections of 2016 as a case study, the study analyzed the relevance of three political dimensions and attitudes for electoral choice: leftwing orientations; attitudes toward government intervention in the economy (“economic statism”); and attitudes toward the discretional use of political power in government (“firm hand”).